Cu‐Catalyzed Chemoselective Preparation of 2‐(Pinacolato)boron‐Substituted Allylcopper Complexes and their In Situ Site‐, Diastereo‐, and Enantioselective Additions to Aldehydes and Ketones. Issue 19 (3rd April 2013) - Meng, Fanke; Jang, Hwanjong; Jung, Byunghyuck; Hoveyda, Amir H.
Abstract : Sustainable, efficient, selective : A three‐component, single‐vessel Cu‐catalyzed method for chemo‐, diastereo‐, and enantioselective conversion of B2 (pin)2, monosubstituted allenes, and aldehydes or ketones to 2‐B(pin)‐substituted homoallylic alkoxides is described. Subsequent functionalization delivers valuable products in up to >98:2 d.r. and 97:3 e.r. (see scheme).